2011
DOI: 10.5194/acp-11-1367-2011
|View full text |Cite
|
Sign up to set email alerts
|

Mass yields of secondary organic aerosols from the oxidation of α-pinene and real plant emissions

Abstract: Abstract. Biogenic volatile organic compounds (VOCs) are a significant source of global secondary organic aerosol (SOA); however, quantifying their aerosol forming potential remains a challenge. This study presents smog chamber laboratory work, focusing on SOA formation via oxidation of the emissions of two dominant tree species from boreal forest area, Scots pine (Pinus sylvestris L.) and Norway spruce (Picea abies), by hydroxyl radical (OH) and ozone (O 3 ). Oxidation of α-pinene was also studied as a refere… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
56
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 67 publications
(86 reference statements)
11
56
0
Order By: Relevance
“…Our results thus suggest that although light intensity and OH-oxidation are important factors controlling nucleation, the growth of the nucleated particles seems to be limited more by the concentrations of the precursor gases and their oxidation by ozone. This is in line with laboratory study by Hao et al (2011).…”
Section: Discussionsupporting
confidence: 74%
“…Our results thus suggest that although light intensity and OH-oxidation are important factors controlling nucleation, the growth of the nucleated particles seems to be limited more by the concentrations of the precursor gases and their oxidation by ozone. This is in line with laboratory study by Hao et al (2011).…”
Section: Discussionsupporting
confidence: 74%
“…Results from EUCAARI show that the yields of biogenic secondary organic aerosol (BSOA) from emissions of Boreal and Mediterranean trees were between 5 and 10 %, independent of the monoterpene mixture (Mentel et al, 2009;Lang-Yona et al, 2010;Buchholz et al, 2011), whereas Hao et al (2011) found a somewhat broader range for the yields (1.9-17.7 %). The formed particle mass and number concentration increased linearly with increasing monoterpene concentrations in accordance with the analysis of Boreal field data by Tunved et al (2008).…”
Section: Bsoa Formation and Oa Partitioningmentioning
confidence: 99%
“…Kuopio showed that even if trace amounts of SO 2 had been present -the modelled peak OH concentration was 1.07 × 10 6 , and it is not likely that sulphuric acid would have been formed enough to produce the observed particle formation rate of 360 cm −3 s −1 without any contribution from the organics. In a later set of experiments (Hao et al, 2011) the ozonolysis products were somewhat surprisingly found to be less volatile than the OH products.…”
Section: Laboratory Experimentsmentioning
confidence: 99%
“…1.9-17.7 % by Hao et al (2011), and 5-10 % from Mentel et al (2009). However, model studies on SOA yields have shown much higher variations and uncertainties, ranging from several percentages up to 70 % (Hallquist et al, 2009).…”
Section: Temperature Influence On the Apparent Aerosol Yieldmentioning
confidence: 99%